Déni et ignorance de l’historicité autochtone dans l’histoire de l’art occidentale - Uzel, Jean-Philippe (RACAR : Revue d'art canadienne / Canadian Art Review, 2017)
Western art history long refused to recognize the historicity of Indigenous art, seeing it instead as a “primitive” mode of human expression. While the dynamism of Indigenous creation since the 1960s has made such an assertion impossible, the institutional recognition given contemporary Indigenous art in the art world is paradoxically accompanied by a lack of critical and theoretical analysis. Today, there is a genuine ignorance concerning Indigenous conceptions of history — their “regime of historicity”— on the part of Western art historians. This is all the more surprising given the recent “temporal turn” taken by the discipline, which emphasizes the question of mixed temporalities without acknowledging it as an essential dimension of Indigenous art. This paper revisits Western art history’s long-standing denial of the historicity of Indigenous art, and then considers its current disregard for the ways Indigenous art allows different forms of temporality to coexist. The underlying thesis of the essay is that today’s disinterest is, in fact, a prolongation of yesterday’s denial.